PENINGKATAN KEMAMPUAN BERPIKIR KRITIS DAN KONSENTRASI BELAJAR SISWA SEKOLAH DASAR MELALUI MODEL PROBLEM BASED LEARNING - Shelva Via Felisa; Asep Sahrul Gunawan (STKIP Subang, 2026)
The low level of critical thinking skills and learning concentration among elementary school students is a common problem in the learning process. This condition is indicated by students’ low participation, easily distracted attention, and limited ability in analyzing and solving problems. Therefore, an innovative and student-centered learning model is needed, one of which is Problem Based Learning (PBL). This study aimed to improve students’ critical thinking skills and learning concentration through the implementation of the Problem Based Learning model. The method used in this study was Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 28 fourth-grade elementary school students. Data collection techniques included observation, tests, and documentation, while data analysis used descriptive quantitative and qualitative approaches. The results showed that the implementation of the Problem Based Learning model was able to improve students’ critical thinking skills and learning concentration. This improvement was indicated by the increase in the average score from 65 in cycle I to 80 in cycle II, while learning mastery increased from 60% to 85%. In addition, the results of observation showed an increase in students’ concentration and active participation during the learning process. Thus, the Problem Based Learning model can be used as an alternative learning strategy to improve students’ critical thinking skills and learning concentration in elementary schools